Internal Conflicts Among Law Enforcement Officials: Professional Integrity or Economic Necessity? - Ratna Kumala Hapsarani (Journal of Human Interaction and Social Studies, 2026)
The effectiveness of law enforcement is fundamentally influenced by the integrity of legal actors who exercise public authority within judicial, prosecutorial, advocacy, and policing institutions. This study examines the phenomenon of internal conflict experienced by law enforcement officers when professional obligations intersect with economic pressures, organizational expectations, and institutional dynamics. Employing a non-empirical legal research design grounded in a normative socio-legal approach, the study utilizes statutory regulations, professional codes of ethics, legal doctrines, scholarly literature, and documented cases involving ethical misconduct, corruption, bribery, and professional violations. The analysis demonstrates that internal conflict emerges from the interaction between normative demands for integrity and socio-economic realities influencing legal decision-making. Existing legal frameworks provide comprehensive obligations concerning professionalism, accountability, and independence; however, persistent ethical violations indicate limitations in the practical internalization of these norms. Institutional culture, discretionary authority, economic incentives, and external influence contribute significantly to integrity-related challenges within law enforcement institutions. The study argues that sustainable law enforcement requires the integration of ethical accountability, effective supervision, institutional independence, and integrity-based organizational governance. Strengthening these dimensions is essential for enhancing public trust, legal legitimacy, and the realization of substantive justice within the rule-of-law framework.